2018
DOI: 10.1016/j.jneuroim.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking interleukin-18 gene display behavioral changes in animal models of psychiatric disorders: Possible involvement of immunological mechanisms

Abstract: Preclinical and clinical evidence suggests pro-inflammatory cytokines might play an important role in the neurobiology of schizophrenia and stress-related psychiatric disorders. Interleukin-18 (IL-18) is a member of the IL-1 family of cytokines and it is widely expressed in brain regions involved in emotional regulation. Since IL-18 involvement in the neurobiology of mental illnesses, including schizophrenia, remains unknown, this work aimed at investigating the behavior of IL-18 null mice (KO) in different pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Behavior was determined using the open field and elevated plus maze (EPM) paradigms as reported [13,28] and described in Supplementary Methods. For the open field test, mice were placed in the corner of the test apparatus and activity was recorded and analyzed using an automated system (VersaMax).…”
Section: Anxiety-like Behaviormentioning
confidence: 99%
“…Behavior was determined using the open field and elevated plus maze (EPM) paradigms as reported [13,28] and described in Supplementary Methods. For the open field test, mice were placed in the corner of the test apparatus and activity was recorded and analyzed using an automated system (VersaMax).…”
Section: Anxiety-like Behaviormentioning
confidence: 99%
“…In a recent study IL-18 deficient mice showed a schizophrenia-like phenotype (higher impulsivity and aggression), but no relevant behavioral changes in tests for anxiety- (EPM) or depression-like behavior (FST) [43]. Also, tumor necrosis factor ko mice did not show alterations in anxiety- and depression-related behavior in the EPM and FST [44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-18KO mice have been shown to become obese and to present with hepatosteatosis, probably because of impaired metabolism of glucose/fatty acids (41,42,64). In addition, IL-18KO mice display altered behaviors that may be related to impaired neurons and damaged mitochondria (34,63). Furthermore, we have previously shown dysfunctions of the heart in IL-18KO mice, probably related to impaired mitochondrial functions (33).…”
Section: Introductionmentioning
confidence: 89%